Staphylococcus aureus lipoproteins in infectious diseases - Mohammad, Majd; Ali, Abukar; Nguyen, Minh-Thu; Götz, Friedrich; Pullerits, Rille; Jin, Tao (Frontiers in Microbiology, 2022)
Infections with the Gram-positive bacterial pathogen Staphylococcus aureus remain a major challenge for the healthcare system and demand new treatment options. The increasing antibiotic resistance of S. aureus poses additional challenges, consequently inflicting a huge strain in the society due to enormous healthcare costs. S. aureus expresses multiple molecules, including bacterial lipoproteins (Lpps), that play a role not only in immune response but also in disease pathogenesis. S. aureus Lpps, the predominant ligands of TLR2, are important for bacterial survival as they maintain the metabolic activity of the bacteria. Moreover, Lpps possess many diverse properties that are of vital importance for the bacteria. They also contribute to host cell invasion but so far, their role in different staphylococcal infections has not been fully defined. In this review, we summarize the current knowledge about S. aureus Lpps and their distinct roles in various infectious disease animal models, such as septic arthritis, sepsis, and skin and soft tissue infections. The molecular and cellular response of the host to S. aureus Lpp exposure is also a primary focus.